Analisis Faktor Internal Terhadap Kinerja Bank Perkreditan Rakyat di Provinsi Jambi - Candy, Candy; Liu, Michelle Selvia; Agustin, Isnaini Nuzula (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2024)
The purpose of this study is to examine internal factors affecting the performance of Rural Credit Banks (BPR) in Jambi province. Internal factors examined include credit risk, liquidity risk, BOPO, debt, intellectual capital, and bank capital. The type of research data used is quantitative data in the form of secondary data, namely published financial reports from 2018 to 2022 on the Financial Services Authority (OJK) website. Based on data from the OJK, there are 19 rural banks in Jambi Province with 95 data used as samples. The analysis was conducted using panel regression through the Eviews software. The results of the analysis indicate that BOPO and bank capital have negative impact on bank performance. On the other hand, debt has a positive effect on bank performance as measured by ROA but a negative effect as measured by ROE. Meanwhile, credit risk, liquidity risk, and intellectual capital do not have a significant impact on bank performance.